Middle Lobe Syndrome: A Case Report and Literature Review - Sciuto, Laura; Tosto, Monica; Licciardello, Laura; Giugno, Andrea; Balconara, Desiree; Mollica, Federico; Mule, Enza; Papale, Maria (Current Respiratory Medicine Reviews, 2024)
Background: Middle lobe syndrome (MLS) is a distinct clinical and radiographic entity characterized by recurrent or chronic collapse of the middle lobe of the right lung, but it can also involve the lingula of the left lung. Case Study: This study presents a rare case of MLS caused by a vascular ring never described in the literature until now and provides physicians with the clinical and instrumental tools in order to early recognize and promptly treat this condition. The case report was reported according to CARE guidelines. A literature research on PubMed/MEDLINE was also performed using the MeSH terms “Middle lobe syndrome OR MLS AND double aortic arch” “Middle lobe syndrome OR MLS AND vascular rings”. No case described in the literature was found. In most cases, MLS presents non-specific respiratory symptoms, which unfortunately is responsible for the diagnostic delay that patients with this pathology often suffer. The diagnostic delay is estimated to be 8 months (range 3 to 36 months). A history of dysphagia and regurgitation can be indirect signs of a vascular compression, such as vascular rings, which can cause MLS. Conclusion: To date, the reported case is the only case in the literature of MLS caused by double aortic arch. The key point for the diagnosis of MLS is diagnostic suspicion. Early recognition of MLS is essential to quickly start a targeted therapeutic program avoiding the persistence of vicious circle atelectasis-recurrent respiratory infections, and this could significantly improve the long-term outcome of these patients.
Keywords: middle lobe bronchus children